'Everywhere they say that it's harmful but they don't say how, so I'm asking here': young people, pornography and negotiations with notions of risk and harm. Issue 2 (3rd March 2016) - Spišák, Sanna
Abstract: Debate about pornography and minors has mainly centred on questions of control, regulation and media policy; the urge to protect children from dangers of sexually explicit content being the primary motivator of these conversations. Instead of discussing the use of pornography by minors in the light of relevant research findings, public discourse on these issues is more usually shaped by views of sexual cultures as inherently dangerous to minors, and young people as vulnerable, easily harmed, and endangered by the media. This paper builds on data consisting of 4212 questions about sexuality that were sent by young people in Finland to experts on sexual health. Only 64 (1.5%) of these contributions explicitly focused on pornography. The small number of porn-related submissions suggests that for young people there are other more important concerns in the field of sexuality than pornography, on which adult guidance is sought. This paper argues that young people's perceptions of pornography are more diverse than is typically assumed in public debate. Young people challenge risk talk by constantly referring to the vagueness of the alleged harm that characterises the discourse of danger that can be found in much public discussion. According to the findings of this study, blurry notions of harm bother young people more than the actual pornographic content they encounter.